1999
DOI: 10.1051/rnd:19990307
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the rat pineal gland by nerve fibres originating in the sphenopalatine, otic and trigeminal ganglia. A retrograde in vivo neuronal tracing study

Abstract: -The innervation of the rat pineal gland from the sphenopalatine, otic, superior cervical and trigeminal ganglia was investigated in animals by use of in vivo retrograde tracings. A solution of 2 % Fluorogold was iontophoretically injected into the superficial pineal gland in a series of Wistar rats. After a survival time of 4-10 days, the animals were fixed by perfusion and the brains, sphenopalatine, otic, superior cervical and trigeminal ganglia were investigated with a fluorescence microscope. Many retrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…However, localization of pinealopetal fibers originating in the pterygopalatine and the otic ganglia (Shiotani et al, 1986;Møller and Liu, 1999) together with the demonstration of pineal cholinergic fibers in the rat (Eranko et al, 1970), ferret (David and Herbert, 1973), rabbit (Romijn, 1973), monkey (David and Kumar, 1978), and cow (Phansuwan-Pujito et al, 1990 have demonstrated the occurrence of a parasympathetic input to the pineal gland. Besides ACh, VIPergic fibers originating from parasympathetic ganglia have also been observed in the rodent pineal gland (Shiotani et al, 1986;Møller and Liu, 1999). In addition, demonstration of receptors and biochemical effects of cholinergic and VIPergic ligands in the pineal gland (see Sections VI.A.…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, localization of pinealopetal fibers originating in the pterygopalatine and the otic ganglia (Shiotani et al, 1986;Møller and Liu, 1999) together with the demonstration of pineal cholinergic fibers in the rat (Eranko et al, 1970), ferret (David and Herbert, 1973), rabbit (Romijn, 1973), monkey (David and Kumar, 1978), and cow (Phansuwan-Pujito et al, 1990 have demonstrated the occurrence of a parasympathetic input to the pineal gland. Besides ACh, VIPergic fibers originating from parasympathetic ganglia have also been observed in the rodent pineal gland (Shiotani et al, 1986;Møller and Liu, 1999). In addition, demonstration of receptors and biochemical effects of cholinergic and VIPergic ligands in the pineal gland (see Sections VI.A.…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
“…Retrograde tracing studies have demonstrated that the trigeminal ganglia project directly to the rodent pineal gland (Shiotani et al, 1986;Reuss et al, 1992a;Møller and Liu, 1999;Reuss, 1999). These fibers contain sP, CGRP, and PACAP.…”
Section: Pathways From Other Neural Structuresmentioning
confidence: 99%
“…Indeed, early studies demonstrated that, besides SCN innervation, the pineal gland receives projections from sphenopalatine, otic and trigeminal ganglia [60], which have been reported to secrete substance P [61]. Recent works demonstrated that pinealocytes are enriched with substance P receptors [62] and that substance P may inhibit norepinephrine-induced AANAT activation and melatonin secretion, though it does not impair basal levels of AANAT functioning [63].…”
Section: Interactions Between Melatonergic System and Monoaminergimentioning
confidence: 99%
“…The SCG, which is a paravertebral ganglion, provides sympathetic input to the head and neck as well as to the mandible, submandibular glands, pineal and eyes (second and third order control) in laboratory animals [Luebke and Wright, 1992;Hubbard et al, 1999;Moller and Liu, 1999;Hayakawa et al, 2000;Ladizesky et al, 2000]. In rats, the SCG is an attractive model because it is easily located and is used as a model to investigate neurobiological disorders.…”
Section: Introductionmentioning
confidence: 99%